Volume Determination of Symmetrical Object with Distance Parameter Using Linear Regression Method - Suseno, Jatmiko Endro; Setyawan, Agus; Gunadi, Isnain (Universitas Dharma Wacana, 2023)
The object’s volume is a consideration in determining the quantity of products such as eggs, fruit, piles of rice, or sand. This research aims to obtain a system for determining the volume of a symmetrical object using the linear regression method in real-time, faster, more effective, and more enjoyable. This research uses segmentation methods and linear regression to determine the volume of a symmetrical object. The objects are a pile of rice and eggs which have symmetrical shapes. The shape of the symmetry in each object is a cone for a pile of rice and an oval for an egg. The results of this research are a system of symmetrical object volume determination using the linear regression method with an accuracy score of 96.48% for piles of rice and 97.84% for an egg. This system has limitations, there are the volume value must be in the data range that has been trained and the camera phone must be the same.